Effect of Training on Employee Performance at PT. Mars Lestari Palembang - Saskia Maharani; Hamid Halin; Juhaini Alie (International Journal of Community Service & Engagement, 2023)
This study aims to analyze the effect of training on the performance of employees of PT Mars Lestari Palembang. The data in this study were obtained through interviews and questionnaires. The research method used in this research is simple linear regression analysis. The results of the study prove that job training (X) has a significant positive effect on employee performance (Y). This research is expected to help companies to improve employee performance through training